Managing Marine Growth on Historic Maritime Structures: An Assessment of Perceptions and Current Management Practices - Baxter, Timothy; Coombes, Martin; Viles, Heather (Frontiers in Marine Science, 2022)
Maritime built heritage (e.g., historic harbors, breakwaters, etc.) is found widely along the coastlines of Europe. Due to its age and traditional construction, built heritage may represent important and largely unidentified hotspots of biodiversity in marine and coastal environments. At the same time, marine growth (e.g., seaweed, mussels, barnacles, etc.) found on these structures may provide both deteriorative and protective functions. To ensure future research focusing on the two-way interactions between marine growth and built heritage addresses the concerns of those responsible for their management, attitudes towards the colonization and growth of marine wildlife must first be evaluated. Such attitudes will shape how marine growth is managed at these sites, which in turn may influence biodiversity and built heritage conservation and any associated values. This study assesses how the growth of sessile species and other surface-colonizing organisms is currently perceived and managed by those responsible for maintaining maritime built heritage, with a particular focus on historic structures constructed of natural stone. Responses from a semi-quantitative online questionnaire of harbormasters, coastal engineers, environmental officers, and heritage managers from around the UK (n = 132) were analyzed alongside a series of semi-structured interviews (n = 29). Our results demonstrate that attitudes towards marine growth are generally in agreement among practitioners irrespective of their occupation or the historic maritime structures they are responsible for managing. Perceptions of marine growth are mostly positive, but concerns exist regarding its impacts on maintenance regimes, the condition of mortar, and health and safety. As well as highlighting opportunities for a more integrated approach to biodiversity and built heritage conservation, the concerns identified require further research attention to help address potential barriers and conflicts that may arise in practice.